Decision-Making and Negotiation in Innovation & Research in Information Science - Sousa, M.; Rocha, Álvaro (Group Decision and Negotiation, 2021)
This Special Issue is dedicated to current issues in Decision-making and Negotiation in Innovation & Research in Information Science. Despite all the research around Decision-making and Negotiation the main theoretical and practical importance of this issue is the focus on studies oriented to innovation & research (I&R) in information science. The purpose is to analyse the decision-making processes for practical problem-solving and to understand the ways information systems can be a trigger in the process. To achieve this objective several articles will present models, tools and frameworks to help improving the decision-making and negotiation processes, and the research findings support the conclusion that information systems can help to achieve better decisions and facilitate the negotiation processes.